Performance Improvement for Wireless Sensor Networks - M. Mijwel, Maad; Q. Shareef, Asmaa (Iraqi Journal of Science, 2023)
In this paper, we prove that our proposed localization algorithm named ImprovedAccuracy Distribution localization for wireless sensor networks (IADLoc) [1] is thebest when it is compared with the other localization algorithms by introducing manycases of studies. The IADLoc is used to minimize the error rate of localizationwithout any additional cost and minimum energy consumption and alsodecentralized implementation. The IADLoc is a range free and also range basedlocalization algorithm that uses both type of antenna (directional and omnidirectional)it allows sensors to determine their location based on the region ofintersection (ROI) when the beacon nodes send the information to the sink node andthe latter sends this information to the sensors by relying on the antenna. Itperformance was compared with previous algorithms HiRLoc, PTA and RAL interms of the number of sensors, average localization error and execution time